2019
DOI: 10.1021/acssuschemeng.9b03263
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Synergistic Effects of Intermolecular Interactions To Synthesize Hybrid Rejuvenators To Revitalize Aged Asphalt

Abstract: This paper examines the merits of using a hybrid bio-oil derived from algae and swine manure to rejuvenate aged bitumen by restoring the bitumen properties which are degraded during oxidative aging. Nitrogencontaining compounds have been found to be effective for decreasing the size of molecular agglomerates which are intensified during aging provided they adequately penetrate into the oxidized asphaltene agglomerations. The enhancement effect is mainly attributed to their electronic structures, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…Based on gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) data analyses, bio-rejuvenator contained a large number of amide and nitrogenous functional groups (Fini et al, 2011;Xiu et al, 2012). Pahlavan et al, 2018Pahlavan et al, , 2019 proposed the molecular structures (Number: BR-1~BR-7) of the main components in bio-rejuvenator. In terms of molecular structure form, these bio-rejuvenator molecules can be divided into straight chains and aromatic compounds.…”
Section: Molecular Structures Of Asphalt Binder and Bio-rejuvenatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) data analyses, bio-rejuvenator contained a large number of amide and nitrogenous functional groups (Fini et al, 2011;Xiu et al, 2012). Pahlavan et al, 2018Pahlavan et al, , 2019 proposed the molecular structures (Number: BR-1~BR-7) of the main components in bio-rejuvenator. In terms of molecular structure form, these bio-rejuvenator molecules can be divided into straight chains and aromatic compounds.…”
Section: Molecular Structures Of Asphalt Binder and Bio-rejuvenatorsmentioning
confidence: 99%
“…It has been demonstrated that amide and nitrogenous molecules are the key components of bio-rejuvenators to exert regenerative effects. The chemical structures of the two active ingredients have been constructed by Farideh Pahlavan et al (2019) and Masoumeh Mousavi et al (2016). Based on MD simulations, Mullins (2010), Li et al (Li andGreenfield, 2014), andGreenfield (2011) have carried out extensive research on the microstructure, component characterization, and simulation treatment of petroleum asphalt binder, providing a methodological basis for the bio-rejuvenator's modified aged asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid rejuvenator showed high resistance towards ageing and moisture damage, whilst concurrently efficient in restoring the rheological properties in aged asphalt. Pahlavan et al [91] assessed the merits of using a hybrid bio-oil rejuvenator derived from algae and swine manure to rejuvenate aged asphalt by restoring the properties of the sample. The proposed rejuvenator indicated more noticeable restoration, along with better de-agglomeration of oxidised asphaltenes.…”
Section: Rejuvenation Of Recycled Asphalt Using Hybrid Rejuvenatormentioning
confidence: 99%
“…During its service life, AC ages as a consequence of the traffic and environmental conditions, determining physico-chemical changes in the bitumen [3]. On the one side, bitumen is subjected to oxidation, i.e.…”
Section: Introductionmentioning
confidence: 99%